"Em queda livre” : vigilância distribuída e “o show do eu” no seriado Black Mirror - Sá, Edilaine Bernardes de (2020)
The purpose of this text is to discuss the distributed surveillance and spectacularization of the self in the episode Black Sky series, Falling Free, directed by Joe Wright, story by Charlie Brooker and script by Michael Schur and Rashida Jones of the year 2016. Episode centered on the ranking social reputation. The episode takes place in a futuristic context, when interactions through digital social networks, more than a way of relating socially, start to determine all aspects of life. People are constantly evaluated by other people; well, the better your evaluation, the higher the “rating” and the more “stars”, consequently, the better your salary, job, and more and better places can be attended. In this episode, the dependence on the social network goes beyond the psychological aspect, becoming a necessity to subsist in society. This episode portrays the indivisibility of the real and virtual worlds, and presents the physical consolidation of a “show of self” and global surveillance. Digital communication technologies are part of the way we understand ourselves in contemporary times, managing and transforming bodies and subjectivities. Therefore, we will employ the methodology of studying scenes through arming games, in front of the science fiction episode “Queda Livre”, by Black Mirror. This methodology is a translation of the method used by Law (2004) to legitimize the multiplicity of realities, whose production, even so, is relatively specific, local and singular. Decomposing the narrative, critical incidents were selected, capable of showing the main tensioning points that make the filmic material can be considered as science fiction (GALINDO; BONNA, 2004; GALINDO, 2016; MEDINA; MEDINA, 2018). In this text, we focus on reputation and moral judgments, issues that have been growing on social media and causing emotional damage or damage to psychological health and self-determination, by decreasing, impairing or disturbing their full development, as they aim to degrade or control actions, through embarrassment, humiliation, manipulation, isolation, constant vigilance or persecution.